THE VALUE OF AN ENTERPRISE AND FORMATION OF REQUIREMENTS TO THE SYSTEM OF ITS ASSESSMENT INDICATORS - Doroshenko, Hanna (Social Economics, 2020)
In modern conditions there is a strong need for theoretical and methodological generalizations and development, as well as practical recommendations, which would be aimed at building an effective mechanism for assessing the value of an enterprise in rapidly changing economic conditions. This study focuses on the part of this problem, especially the identification of the requirements to be met by the indicators used for such an assessment. In addition, in order to avoid unilateralism, the main approaches to determining the value of an enterprise are considered and its types are defined in the article. In our work, we rely on the concept of «enterprise value» in its broad sense. Value is a characteristic of production process encapsulated in economic well-being, which expresses its internal potential ability to bring effect that exceeds not only the cost of creating this benefit, but also its opportunity value, i.e. the benefit of lost opportunities as a result of investing resources in production of this benefit. The value becomes socially recognized if it allows the resource owner to have this effect in the form of accumulated economic added value based on economic profit. However, no matter what approach is used, the value of the assessment will depend on the right indicators that allow to make an analysis and to provide objective results. The main features of the system of indicators for assessing the value of an enterprise are: adequacy, accuracy, objectivity, trustworthiness, unambiguity, profitability, value, compatibility, timeliness and regularity, defining cause-and-effect links and indicators of assessment and evaluation of business opportunities. Taking into account the above-mentioned, the following conclusions are made: the choice of indicators for value assessing is individual in nature, as there are specific characteristics of appraisal objects and current and strategic objectives of the appraisal; to form a system for assessing the value of a particular joint-stock company, it is necessary to take into account the development or absence of market institutions, environment, factors of their stability, level of business capitalization, degree of control, etc.; usage (application) of a balanced system of assessment indicators should be the basis for making managerial decisions. The perspective for further research in this area needs to be guided in the development of tools for assessing the value of enterprises, as well as improving the integrated assessment of financial and economic conditions and efficiency of enterprise management, based on the highlighting of the most influential indicators of financial, property and management nature taking into account the specificity of an entity activity.